Spathe morphology of Commelina L. (Commelinaceae) of India in relation to Taxonomy - Joseph, Sheba M.; Nampy, Santosh (Botanica Orientalis: Journal of Plant Science, 2015)
Commelina L., the largest genus of Commelinaceae, is easily distinguished from related genera by inflorescence subtended in a folded bract (spathe). The position, number, size, shape, hairiness, cincinnus number and peduncle length of the spathe are useful in species delimitation. In the present investigation, twenty four species of Commelina occurring in India are studied for spathe characters and their significance in taxonomy is discussed. A key for the identification of all species based on spathe characters is also provided. Botanica Orientalis – Journal of Plant Science (2015) 9: 1–11